TANGGUNG GUGAT ASURANSI TERHADAP KERUSAKAN LINGKUNGAN HIDUP DI INDONESIA - hermawan, sapto -; Rakasiwi, Deviana Az Zahra; Khayanto, Miftah Nur; Ridhlo, Muhammad Rosyid (Indonesian State Law Review (ISLRev), 2021)
Insurance liability for environmental damage has been accommodated in Law Number 32 of 2009 concerning Environmental Protection and Management. However, in its implementation there are still many shortcomings and obstacles, both internal and external factors. This journal discusses the implementation of insurance liability for environmental damage in Indonesia according to Law No. 32 of 2009 and the development of the implementation of insurance liability in Indonesia for environmental damage compared to Singapore and Poland. To obtain complete and accurate data in this study, the author uses normative or doctrinal legal research. Environmental Insurance is very important. However, in its development, environmental insurance is still considered new for Indonesian citizens. In its own implementation environmental insurance is still not going well due to various obstacles, one of which is the lack of regulations regarding environmental insurance. The same thing happened in Singapore, where there was still a lack of regulation or implementation, in contrast to Poland, which already had awareness about the importance of good environmental insurance.